KARAKTERISTIK FISIK, KIMIA DAN ORGANOLEPTIK PEMPEK DENGAN SUBSTITUSI TEPUNG MOCAF (modifie cassava flour) - Dasir Dasir; Suyatno Suyatno; Sri Agustini; Ahmad Robi A.P. (Balai Riset dan Standardisasi Industri Palembang, 2022)
This study aims to determine the physical, chemical and organoleptic quality of pempek from various comparisons of mocaf with tapioca. The study was conducted using a non-factorial randomized block design with five levels of treatment, namely M0 (0% mocaf and 100% tapioca), M1 (25% mocaf and 75% tapioca), M2 (50% mocaf and 50% tapioca), M3 (75% mocaf and 25% tapioca), and M4 (100% mocaf and 0% tapioca), with four repeated. The research data were analyzed by ANOVA and further test with a real difference honestly. The results showed that the higher the percentage of mocaf used, the higher the protein and fiber content. The highest protein and fiber content were 9.15 % and 1.88% respectively in the M4 treatment with a score of 4 color, aroma, taste values (preferred by panelists) and the best level of elasticity. Based on the results of the study, it was concluded that the higher the substitution of mocaf flour, the higher the protein content and fiber content, but the highest preference values for the hedonic test of color, taste, aroma and elasticity test resulted in the lowest substitution of mocaf flour M1 (25% moca and 75% tapioca).